Transferability of Ancestry‐Specific and Cross‐Ancestry CYP2A6 Activity Genetic Risk Scores in African and European Populations. Issue 4 (1st January 2021) - El‐Boraie, Ahmed; Chenoweth, Meghan J.; Pouget, Jennie G.; Benowitz, Neal L.; Fukunaga, Koya; Mushiroda, Taisei; Kubo, Michiaki; Nollen, Nicole L.; Sanderson Cox, Lisa; Lerman, Caryn; Knight, Jo; Tyndale, Rachel F.
Abstract : The Nicotine Metabolite Ratio (NMR; 3‐hydroxycotinine/cotinine), a highly heritable index of nicotine metabolic inactivation by the CYP2A6 enzyme, is associated with numerous smoking behaviors and diseases, as well as unique cessation outcomes. However, the NMR cannot be measured in nonsmokers, former smokers, or intermittent smokers, for example, in evaluating tobacco‐related disease risk. Traditional pharmacogenetic groupings based on CYP2A6 * alleles capture a modest portion of NMR variation. We previously created a CYP2A6 weighted genetic risk score (wGRS) for European (EUR)‐ancestry populations by incorporating independent signals from genome‐wide association studies to capture a larger proportion of NMR variation. However, CYP2A6 genetic architecture is unique to ancestral populations. In this study, we developed and replicated an African‐ancestry (AFR) wGRS, which captured 30–35% of the variation in NMR. We demonstrated model robustness against known environmental sources of NMR variation. Furthermore, despite the vast diversity within AFR populations, we showed that the AFR wGRS was consistent between different US geographical regions and unaltered by fine AFR population substructure. The AFR and EUR wGRSs can distinguish slow from normal metabolizers in their respective populations, and were able to reflect unique smoking cessation pharmacotherapy outcomes previously observed for the NMR. Additionally, we evaluated the utility of a cross‐ancestry wGRS, and the capacity of EUR, AFR, and cross‐ancestry wGRSs to predict the NMR within stratified or admixed AFR‐EUR populations. Overall, our findings establish the clinical benefit of applying ancestry‐specific wGRSs, demonstrating superiority of the AFR wGRS in AFRs.